Biofungisida Berbahan Aktif Eusiderin I Untuk Pengendalian Layu Fusarium Pada Tomat - Harizon, Harizon (Biospecies, 2009)
This reserach aims to develop a new fungicide formula with active agent Eusiderin I toinhibit Fusarium oxysporum f.sp. lycopersici that causing fusarium wilt on tomato. This researchincludes isolation Eusiderin I from bulian wood, growing potato in green house, reproduction ofFusarium oxysporum f.sp. lycopersici, eusiderin I stability test, bioacitivity test of the Fusarium in agreen house. This research succesfuly formulates an emulsifiable concentrate fungicide with activematerial Eusiderin I. The fungicide formula is composed of active material, solvent, and emulsifier.Eusiderin I 3 ppm proves the highest efication, indicated by only a tomato plant dead in eachtreatment (p<0.05). It was concluded that . fungicide with active content Eusiderin I on 3, 4, and 10ppm affect on the number of survived tomato plants. The efication degree of this fungicide on 3, 4,5, and 10 ppm is not significantly different.